2014
DOI: 10.18632/oncotarget.2311
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of a TM4SF5-specific monoclonal antibody against colon cancer in a mouse model

Abstract: Transmembrane 4 superfamily member 5 protein (TM4SF5) is presumed to serve as a molecular target to prevent or treat hepatocellular carcinoma (HCC) and colon cancer in a mouse model. Previously, we reported the efficacy of anti-cancer peptide vaccine targeting TM4SF5. In addition, we reported an anti-proliferative effect of anti-TM4SF5 monoclonal antibody in HCC. Here, we investigated expression of TM4SF5 in 45 primary colon cancer tissues. Almost all of the colon cancer tissues expressed TM4SF5 based on immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…We previously confirmed that treatment with the anti-TM4SF5 monoclonal antibody reduced the growth of human and mouse colon cancer cells [15]. Here, we found that the treatment of colon cancer cells with the humanized anti-TM4SF5 antibody significantly reduces their migration capability, based on the results from migration and wound healing assays.…”
Section: Discussionsupporting
confidence: 80%
“…We previously confirmed that treatment with the anti-TM4SF5 monoclonal antibody reduced the growth of human and mouse colon cancer cells [15]. Here, we found that the treatment of colon cancer cells with the humanized anti-TM4SF5 antibody significantly reduces their migration capability, based on the results from migration and wound healing assays.…”
Section: Discussionsupporting
confidence: 80%
“…Previously, we screened an efficacious B-cell peptide epitope (hTM4SF5R2-3) by immunizing BALB/c mice with various TM4SF5 peptides and characterized the prophylactic and the therapeutic effects of the peptide vaccine on hepatocellular carcinoma and colon cancer cell lines and tumor mouse models (8,9,25). We also produced TM4SF5-specific monoclonal antibodies and evaluated their therapeutic effects (18,19,26). Based on these data, we hypothesized that the hTM4SF5 protein is a reasonable target for anticancer therapy and that anti-hTM4SF5 antibodies warrant further development as therapeutic agents for the inhibition of hTM4SF5 function in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the specificity of its targeting and its internalization into cells, the development of antibody-drug conjugates of mEC2-CF may be an alternative strategy for its application in anticancer therapeutics. Previously, we demonstrated a higher expression of hTM4SF5 in colon cancer tissues compared to normal tissues by analyzing commercially-available tissue microarrays using immunohistochemistry (18). The vendor provided information regarding sex, age, tumor grade, along with the tumor, node and metastasis (TNM) stage of the tissues included in the microarray.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations